Metodología para el desarrollo de un sistema de gestión del riesgo operativo aplicado a cooperativas de ahorro y crédito reguladas por la superintendencia de bancos y seguros en la ciudad de Loja - Ludeña Encalada, Over Nixon (2016)
Knowing the reality and operational risks to which they are exposed financial institutions and referring to the segment of the study, which is focused on our theme such as the Credit Unions , we have developed this proposed methodology in the field of Operational Risk Management , for it began with the identification of existing and legal framework, the same as after integration and discernment allowed to adopt an adaptive methodology credit unions to the effect were intensive literature research activities . The organizational scheme that allows for proper operational risk management was proposed based on a simulation of organizational structure , whereby the different instances of a cooperative entity identified was assigning the respective responsibilities in each of the phases of the risk management operating , the proposal also determines the organizational structure or approach to implement if not available. The proposed methodology for the identification and measurement of operational risk was selected considering the initial level of maturity in which cooperative entities for operational risk management , for which an analytical model arises through risk matrices are located to be applied in the process , however the methodology can be applicable in analysis of new products , projects, etc. The schema information for operational risk management proposal was outlined based on certain guidelines set forth in the standard operational risk , however customization of reports classifying in which should be directed to senior management was applied with respect to targeting process leaders for control and risk management. Finally defining alternatives to the culture of operational risk management has been proposed based on the authors' own initiatives , who believe that an incentive scheme is the most appropriate strategy to generate culture where issues are identified ongoing training staff the entity definition of risk acceptance policies , communication and ongoing monitoring , among others, all with the full support of senior management.